1998
DOI: 10.1002/(sici)1521-3803(199812)42:06<385::aid-food385>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of saliva dilution on the release of diacetyl and 2-heptanone from cream style dressings

Abstract: Aroma release from a cream style dressing, consisting of a thickening agent dispersed in the water phase of an oil in water (o/w) emulsion, has been studied by a purge-and-trap (PT) and a dynamic headspace mastication (DHM) model using two representative volatile compounds, viz. diacetyl and 2-heptanone. These isolations have been carried out from three systems: the dressing, the thickening agent dispersion and the o/w type of emulsion after adding different volumes of artificial saliva. Dilution of the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 8 publications
(9 reference statements)
1
25
0
Order By: Relevance
“…The strategies can be divided into two groups: those ones that give a snapshot of the composition of the vapours above the product or streamed out of the product and those others which can provide a continuous monitoring of the composition of those vapours. In the first category, the most common approach is headspace solidphase microextraction (SPME) [12,13], although other techniques such as dynamic headspace extraction methods coupled to gas chromatography (GC) have been also applied [14,15]. In the second category we find direct atmospheric-pressure chemical ionization mass spectrometry (APCI-MS) [8,[16][17][18][19] and proton transfer reaction mass spectrometry (PTR-MS) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The strategies can be divided into two groups: those ones that give a snapshot of the composition of the vapours above the product or streamed out of the product and those others which can provide a continuous monitoring of the composition of those vapours. In the first category, the most common approach is headspace solidphase microextraction (SPME) [12,13], although other techniques such as dynamic headspace extraction methods coupled to gas chromatography (GC) have been also applied [14,15]. In the second category we find direct atmospheric-pressure chemical ionization mass spectrometry (APCI-MS) [8,[16][17][18][19] and proton transfer reaction mass spectrometry (PTR-MS) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of saliva composition and ratio on the release of volatile compounds has been studied by several authors [4,[6][7][8]10]. In general, saliva produces changes in the release of flavour compounds depending on saliva flow and composition which at the same time is affected by the nature of the stimulus that generates extra saliva on mastication [1].…”
Section: Introductionmentioning
confidence: 98%
“…Several studies were done in liquid systems such as oil and oil in water emulsions [4,7] and in mixtures of sucrose and cyclamate [11]. Other studies were performed in semi-liquid foods such as cream style dressings [10,12] or aqueous solutions [2,9]. Only a few studies were done with solid foods, French beans [5,7] and bananas [8].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of artificial saliva has been studied on odorant solutions (Friel & Taylor, 2001;Roberts & Acree, 1995) and on semi-solid matrices (Hansson et al, 2003;Odake, Roozen, & Burger 1998;Odake, Roozen, & Burger 2000;van Ruth & Roozen, 2000;van Ruth et al, 1995b). It was shown that the effect of saliva composition varies greatly depending on the compounds studied (Friel & Taylor, 2001) and the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the effect of saliva composition varies greatly depending on the compounds studied (Friel & Taylor, 2001) and the matrix. Indeed, while Odake et al (1998) showed an influence of artificial saliva on the release of odorant compounds from salad dressings, Rabe et al (2004) showed no effect of saliva addition on the release of volatile compounds from water and aqueous starch hydrolysate. In some of these studies, the impact of each saliva component was determined separately.…”
Section: Introductionmentioning
confidence: 99%